IMPLEMENTASI KEBIJAKAN TATA CARA PENERBITAN/PERUBAHAN KARTU KELUARGA DI KECAMATAN BANGSRI KABUPATEN JEPARA - Fadiya Aisa Puspita Seyasty; Herbasuki Nurcahyanto; Aufarul Marom (Journal of Public Policy and Management Review, 2022)
Implementation of policy on issuance/change procedures of KK in Bangsri Subdistrict is guided by Jepara Regent Regulation Number 27 of 2017 concerning Requirements and Procedures for Population Registration and Civil Registration. Based on this regulation, the implementation of the issuance/change of KK in Bangsri Subdistrict cannot be separated from the cooperation between the Villages in Bangsri Subdistrict and the Disdukcapil of Jepara Regency, but in its implementation there are several processes that are not in accordance with these regulations, namely making KK application forms and recording important events and population events. in the village; entry of population data, signing of the KK application form by the Camat and submission of KK in the District; and receipt of population data recording at the Disdukcapil, besides that there are problems that occur in every process of issuance/change of KK. This study aims to analyze the implementation of the policy on the issuance/change of KK in Bangsri District, Jepara Regency and the inhibiting and supporting factors in the implementation of the policy. This type of research is descriptive qualitative with informant selection techniques, namely purposive and accidental sampling. The results of this study indicate that the discrepancy in the process of issuing/changing KK in Bangsri District is due to adjustments to technological advances, the delegation of some of the authority of the Regent to the Camat, and the existence of Permendagri Number 108 of 2019 and the problems that occur in each process are due to the inhibiting factors, namely communication, sources power, and bureaucratic structure, in addition, there is a driving factor, namely disposition. Researchers provide suggestions, namely improving the quality and quantity of human resources, adding facilities, conducting socialization, updating the SOP for KK Services, the need for a regulation to change the Perbup Jepara Number 27 of 2017.